ANALISIS MOTIVASI BELAJAR SISWA DI ERA KURIKULUM MERDEKA - Oktayani, Eka; Andriani, Putri; Ikhsan, M Firman Al; Abdurrahmansyah, Abdurrahmansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Student learning motivation is a crucial factor in achieving quality educational outcomes. The implementation of the Independent Curriculum, which emphasizes flexibility, student-centered learning, and holistic competency development, is expected to bring significant changes to learning motivation. Although it aims to increase interest and intrinsic motivation through the freedom to choose materials, methods, and evaluations, this transition also presents challenges that can affect student motivation in various ways. This article, based on a comprehensive literature review, aims to deeply analyze the dynamics of student learning motivation in the Independent Curriculum era. This study covers the basic concepts of learning motivation (definition, function, principles, improvement strategies) and examines the important role of teachers and the implementation approach of the Independent Curriculum—such as personalization, the Pancasila Student Profile Strengthening Project (P5), personal approach, and active learning—in fostering motivation. It is hoped that this article will provide significant understanding and practical implications to support improving the quality of education in Indonesia by strengthening student learning motivation within the framework of this new curriculum. ABSTRAKMotivasi belajar siswa merupakan faktor krusial dalam mencapai hasil pendidikan berkualitas. Implementasi Kurikulum Merdeka, yang menekankan fleksibilitas, pembelajaran berpusat pada siswa, dan pengembangan kompetensi holistik, diharapkan membawa perubahan signifikan terhadap motivasi belajar. Meskipun bertujuan meningkatkan minat dan motivasi intrinsik melalui kebebasan memilih materi, metode, dan evaluasi, transisi ini juga menghadirkan tantangan yang dapat memengaruhi motivasi siswa secara beragam. Artikel ini, berdasarkan kajian literatur komprehensif, bertujuan menganalisis secara mendalam dinamika motivasi belajar siswa di era Kurikulum Merdeka. Kajian ini mencakup konsep-konsep dasar motivasi belajar (definisi, fungsi, prinsip, strategi peningkatan) serta mengkaji peran penting guru dan pendekatan implementasi Kurikulum Merdeka—seperti personalisasi, Proyek Penguatan Profil Pelajar Pancasila (P5), pendekatan personal, dan active learning—dalam menumbuhkan motivasi. Diharapkan artikel ini memberikan pemahaman signifikan dan implikasi praktis untuk mendukung peningkatan kualitas pendidikan di Indonesia melalui penguatan motivasi belajar siswa dalam kerangka kurikulum baru ini.